Income Analysis And Level Of Welfare Rice Farmers Field (Oryza Sativa L) In The Village Waenetat District Waeapo - Sinta Wahyuni; Jeter D. Siwalette; Marfin Lawalata (International Journal of Economics, Business and Innovation Research, 2022)
This study aims to determine the production, income, and level of household welfare of farmers. The number of samples taken were 42 farmers who were selected intentionally (purposively). The data collected are primary data and secondary data. The method used in this research is the interview method, the observation method and the questionnaire method. The data analysys used in this research is quantitative analysis. The results showed that the average rice production was 2.401 kilograms per hectare per growing season. The average income of respondents is Rp. 8.188.267,-/hectare per growing season. The welfare level of farmer household is in the prosperous category.